Consumer behavior (Henry Stewart Talks, 2026)
Disciplines influencing consumer behavior, Consumer decision process stages, Psychological, social, situational influences, Sensory marketing and emotional drivers, Digital transformation, social media impact, Personalization and data ethics in marketing